2022
DOI: 10.3390/met12040587
|View full text |Cite
|
Sign up to set email alerts
|

Initiation Mechanism of Localized Corrosion Induced by Al2O3-MnS Composite Inclusion in Low-Alloy Structural Steel

Abstract: The present work systematically investigated the initiation mechanism of localized corrosion induced by Al2O3-MnS composite inclusion in E690 steel under a simulated marine environment. The results showed that a micro-gap exists between the Al2O3-MnS inclusion and the matrix, and electron backscattered diffraction (EBSD) analysis revealed significant lattice dislocation zones around the Al2O3-MnS composite inclusion. The presence of the micro-gap and the lattice dislocation both promoted the localized corrosio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The slatted bainite organization of the E690 alloy fine-tuned steel, which consists of fine M/A island particles arranged in an orderly manner, may have contributed to its superior corrosion resistance compared to the traditional ferrite + pearlite organization found in weathering steel [41]. The results also suggest that the corrosion activity of 2# steel is initially slightly higher than that of 1# steel but becomes significantly lower with prolonged immersion time.…”
Section: Discussionmentioning
confidence: 80%
“…The slatted bainite organization of the E690 alloy fine-tuned steel, which consists of fine M/A island particles arranged in an orderly manner, may have contributed to its superior corrosion resistance compared to the traditional ferrite + pearlite organization found in weathering steel [41]. The results also suggest that the corrosion activity of 2# steel is initially slightly higher than that of 1# steel but becomes significantly lower with prolonged immersion time.…”
Section: Discussionmentioning
confidence: 80%
“…After a series of immersion tests and characterizations, it was found that MnS did preferentially dissolve (the signals of Mn and S elements cannot be detected after 15 min immersion in an aggressive solution). Nevertheless, the localized corrosion triggered by inclusions did not terminate, especially the detection signals of Al and O elements were weak after immersion for 30 min, which fully 16,21 .…”
Section: Interphase Defects-triggered Selective Dissolutionmentioning
confidence: 98%
“…As depicted in Fig. 14, a Al 2 O 3 -MnS complex inclusion-triggered localized corrosion system involved in some investigations is a representative case in terms of the above situation 16,21 . Volta potential measurement and conductivity test determine the insulating properties of Al 2 O 3 , and also confirm the illustration in Section 3.2 that conductive MnS inclusions often act as an anode in stainless steel (Fig.…”
Section: Interphase Defects-triggered Selective Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Al 2 O 3 and RE oxide particles that participate in the initial pitting corrosion, although micro acidic region can be generated [4,35], Cu is not enriched or less enriched due to their small number and immovable Cu atoms, as shown in figures 13(a) and (b). For Al 2 O 3 particles that do not participate in the initial pitting corrosion, a micro acid region cannot be formed around them owing to their high stability [4,33,40]; thus, Cu is not enriched (figure 13(c)). However, RE oxide particles that do not participate in the initial pitting corrosion can decompose and a micro acid region is formed [35]; therefore, Cu is enriched (figure 13(d)).…”
Section: Mechanism Of the Distribution Of Cu Element In The Steel And...mentioning
confidence: 99%